Characterization of Mannanase-Producing Bacteria from Porang Tubers (Amorphophallus muelleri Blume): Karakteristik Bakteri Penghasil Mannanase dari Umbi Porang (Amorphophallus muelleri Blume) - Utami, Dwi Retnaningtyas; Prayitno, Sutrisno Adi; Rahim, Andi Rahmad; Ningrum, Sugiyati; Putri, Silvy Novita Antrisna; Patria, Domas Galih (jurnal makanan tropis dan teknologi agroindustri, 2024)
Porang tubers have the potential as a source of carbon and energy for the growth of mananolytic bacteria. Mananolytic are bacteria producing mananase enzymes that are able to break down manan compounds and their derivatives. Mananase can be widely applied in the food, pharmacy, animal feed sectors, paper industries and many more. In this study, Ai isolate have been isolated and characterized, porang tubers are used as substrates for measuring the activity of mananase. The optimum temperature mananase at 40 ° C, stable at a temperature of 30 ° C-50 ° C, have optimum pH 7 and are stable at pH 4-7. Fe2+ was an activator, while Ca2+ and Mg ions were inhibitor of mananase.